La llengua abans de la lingüística, arran d’unes notes d’Antoni de Bastero - Rafanell, August; Feliu, Francesc (Caplletra. Revista Internacional de Filologia, 2001)
Starting with the as yet unpublished writings of the scholar, Antoni de Bastero, the authors reflect on this Catalan author’s interest on dialectal aspects of the Catalan language. This would place Bastero in the state-of-the-arts of dialectology in this country.